The effect of contrast water therapy on high intensity cycling performance - A doseresponse study - Versey, N.; Halson, S.; Dawson, B. (National Elite Sports Council 2009 Athlete Services Forum - High Performance Programming for Success - 11-12th November - Satellite Program - Applied Physiology Conference 2009 - Australian Institute of Sport, Canberra - 10th, 11th and 13th November, 2009)
Contrast water therapy (CWT) is increasingly being used by elite athletes to accelerate recovery processes. Scientific evidence exists to show that CWT improves post exercise recovery and subsequent exercise performance (2,3,4,5) however, the optimal CWT protocols remain unclear. The purpose of the present study was to determine if CWT has a dose-response affect on recovery from high intensity cycling performance. Methods Eleven male trained cyclists (Age: 32.1 ± 7.6 yrs, VO2max: 64.5 ± 5.4 ml/kg/min) performed two familiarisations and four trials that differed only in the recovery protocol. Each trial commenced with a cycling protocol designed to simulate the demands of cycling races and produce fatigue. The protocol was 109 min in duration, including 66 maximal effort sprints of 5 - 15 sec duration and 3 × 5 min maximal time trials. Ten minutes post exercise subjects performed one of four recovery protocols in randomised, counterbalanced order. Each subject performed three CWT trials for 6 (CWT6), 12 (CWT12), and 18 min (CWT18) duration. The CWT commenced in the hot water (38 ºC) and alternated between the hot and cold water (14 ºC) every minute with a 5 sec changeover. Each subject also performed a control trial. The cycling protocol was repeated two hours after the completion of the first exercise bout. Subjects consumed water ad lib during each trial. Immediately post recovery subjects consumed fluid and food containing 2 g of carbohydrate per kilogram body mass in order to replace glycogen stores. The following measures were made during the study: power output, heart rate, rectal temperature, rating of perceived exertion, muscle soreness, fatigue, thermal sensation, effort, and motivation. A post only analysis was conducted using the pre test as a covariate and magnitude based inferences (1). Results Only the performance data is reported in this abstract due to space limitations. The total work produced during the 15 sec sprints (Fig. 1) was greater in the CWT trials than the control trial (CWT6: 3.0 % ± 3.1 %, CWT12: 4.3 % ± 3.4 %, CWT18: 2.5 %± 4.7 %, % change ± 90 % confidence limits). The average peak power output for the 15 sec sprints was greater during the CWT12 trial compared to the control trial (2.7 % ± 3.8 %, % change ± 90 % confidence limits). All other effects were unclear. All differences between trials in the total work produced during the 5 min time trials were also unclear (Fig. 2). Discussion/Conclusion Contrast water therapy may improve recovery from sprint cycling exercise by a small amount however, it has no effect on 5 min time trial performance. A dose-response relationship does not exist between CWT recovery duration and subsequent high intensity cycling performance.